2008
DOI: 10.1115/1.2948358
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Velocities in Two-Phase Flow by Laser Velocimetry: Interaction Between Solid Particles’ Motion and Turbulence

Abstract: In this work, an experimental method based on laser anemometry with Doppller effects is developed. This allows the measurement of velocities and their fluctuations in a flow of solid-liquid suspension in an ascendant vertical pipe. In order to distinguish between the signals coming from the continuous phase, water, and those of the glass bead particles larger than the Kolmogorov length scale, an electronic logic circuit was incorporated in the measuring equipment. This enabled the study of both the slip veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The varying trends in the turbulence modulation in these experimental data are therefore likely caused by the difference in their Re. Importantly, turbulence enhancement in dilute-phase liquid-particle pipe flows at low Re (E16,000) has also been experimentally observed by Chemloul and Benrabah (2008).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The varying trends in the turbulence modulation in these experimental data are therefore likely caused by the difference in their Re. Importantly, turbulence enhancement in dilute-phase liquid-particle pipe flows at low Re (E16,000) has also been experimentally observed by Chemloul and Benrabah (2008).…”
Section: Introductionmentioning
confidence: 81%
“…In the present work, CFD model predictions, however, are not validated Table 1 A summary of the flow characteristics of the Alajbegovic et al (1994) and Hosokawa and Tomiyama (2004) using the experimental data of Chemloul and Benrabah (2008) because they exhibit slightly lower St T , Re T , and Re P ( E15, 50, and 100, respectively) than the respective values in Alajbegovic et al (1994) and Hosokawa and Tomiyama (2004), such that the Re effect on the turbulence modulation cannot be truly isolated.…”
Section: Introductionmentioning
confidence: 93%
“…Sad-chemloul and Benrahah (2008) showed that for fine particles the suspension behaves like a homogeneous fluid, while for large particles existence of a slip velocity is responsible for the fluid-particle interaction. Muste et al (2009) show that irrespective of particle specific gravity, the bulk velocity of flow in particle-laden flows is reduced; the linear Reynolds stress variation is preserved in dilute particle-laden flows, and the streamwise mean velocities of particles exceed those of water near the wall.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…Besides the particles acceleration in the vortex, in our view, when the particle size is less than the Kolmogorov scale, the strong interaction between particles and turbulence vortexes is produced. Under the action of the relative velocity as pointed out by Sad-chemloul and Benrahah (2008), the small particles might penetrate through vortexes of different sizes back and forth, which might be able to decay them, resulting in the suppression of the liquid turbulent intensities. The detailed studies on the particles in or together with vortexes need to be further performed in the following work.…”
Section: Particle Modulation On the Liquid Turbulencementioning
confidence: 99%
“…Solid-liquid two-phase flows are frequently observed in many industrial processes and natural phenomena (Kaftori et al, 1995a(Kaftori et al, , 1995bPan and Banerjee, 1996;Li et al, 1999;Kiger and Pan, 2002;Zheng, 2004;Sad-Chemloul and Benrahah, 2008;Muste et al 2009). In particular, cylindrical particles play an important part in the production of composite materials.…”
Section: Introductionmentioning
confidence: 99%